2018
DOI: 10.1016/j.cej.2017.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-derived N-doped porous carbon as electrode materials for Zn-air battery powered capacitive deionization

Abstract: Capacitive deionization (CDI) has been a promising technique to obtain fresh water by electrosorption of charged ionic species in seawater/brackish water. Its performance is highly dependent on the physical and chemical properties of CDI electrode materials. Herein, Ndoped porous carbon (NPC) with a N content of 1.66 at.% was fabricated using soybean shell as starting material by a facile pyrolysis approach with the assistance of KHCO 3 in N 2 atmosphere. The as-prepared NPC with porous structure and high surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(59 citation statements)
references
References 65 publications
2
56
0
1
Order By: Relevance
“…[48,49] This leavening strategyh as proved to be ag reen and sustainable process for the effective and convenient conversion of awide variety of biomass derivativesa nd crude biomass into functional HPC materials.S ince the group of Wang developed the leavening strategy,s everalp apers have been published on the use of KHCO 3 as an activating agenti nt he preparation of porous carbon materials, derived from hydrochar and biomass waste, as electrode materials for supercapacitors, lithium-ion batteries, and capacitive deionization. [50][51][52][53] However,K HCO 3 is still used much less than KOH, and therefore, there will be considerable room for chemical activation by KHCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[48,49] This leavening strategyh as proved to be ag reen and sustainable process for the effective and convenient conversion of awide variety of biomass derivativesa nd crude biomass into functional HPC materials.S ince the group of Wang developed the leavening strategy,s everalp apers have been published on the use of KHCO 3 as an activating agenti nt he preparation of porous carbon materials, derived from hydrochar and biomass waste, as electrode materials for supercapacitors, lithium-ion batteries, and capacitive deionization. [50][51][52][53] However,K HCO 3 is still used much less than KOH, and therefore, there will be considerable room for chemical activation by KHCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the surface modification by heteroatom incorporation and the chemical conversion from low‐cost biomass precursors into high value‐added carbon materials have been investigated as emerging CDI technologies. Chang et al demonstrated N,S‐codoped carbon materials through a ball milling and heat treatment of polymers such as polyvinyl dichloride.…”
Section: Carbon Materials For Sodium Capture By Capacitive Deionizationmentioning
confidence: 99%
“…These findings indicate that the facile and cost effective synthesis of carbon materials with a large surface area and multiple heteroatom doping resulted in achieving a high removal efficiency of CDI. Zhao et al prepared biomass‐derived N‐doped porous carbons (NPCs) for CDI system powered by the Zn–air battery. NPCs with an N content of 1.66 at% were synthesized uniformly mixing and thermally treating soybean shell with potassium bicarbonate.…”
Section: Carbon Materials For Sodium Capture By Capacitive Deionizationmentioning
confidence: 99%
“…Zhao等 [80] [63] (网络版彩图) 图 6 纤维素氨基甲酸酯作为先驱体、尿素作为氮源、 NaOH作为溶剂和活化剂制备分级多孔的N掺杂的碳材料的 示意图 [79] (网络版彩图) 报道了 采用三种不同的物质作为碳源, 通过磷酸活化的方法, 图 7 B掺杂的有序介孔碳材料的形成 [86] (网络版彩图) [29] (网 络版彩图) Figure 8 The synthetic process of Pt/POMCs [29] (color online). 图 9 制备S掺杂的有序介孔碳材料的示意图 [90] (网络版彩 图) Figure 9 Cartoon illustrating the synthetic process of OMC-S [90] (color online).…”
Section: 环氧乙烷-聚环氧丙烷-聚环氧乙烷(Peo-peo-unclassified